Psychopathic behavior in Gone Girl movie - Evia Nurdiarti Aditira; Vita Vendityaningtyas (English Teaching Journal : A Journal of English Literature, Language and Education, 2018)
This research deals with analyzing psychopathic behavior in Gone Girl movie. It is reflected through the main female character, Amy Elliott Dunne. The research problems are to find the characteristics of Amy’s psychopathic behavior and to find the causes of her psychopathic behavior. In this research, the researchers use qualitative research method. The main data is Gone Girl movie. It is supported by secondary data such as books, articles appropriate with this research. In collecting the data, the researchers use documentation technique. Content analysis is chosen by the researchers to analyze the data. The results of this research are described as follows: 1) Amy has great obsession about herself that leads her to commit crimes. She senselessly slits the throat of the victim only by using a cutter. She does manipulative act and exposes sexual appeal to the victim. Amy also makes public opinion that her husband kills her. In the end, she creates herself as innocence for the murder of Desi, her ex-boyfriend. She twists the story that she has been raped and kidnapped by him. 2) Amy’s psychopathic behavior is believed to be affected by her surrounding, especially her parents. Amy's family is full of manipulative acts. Amy’s parents utilize Amy to be an amazing person who inspires many people by creating a storybook entitled "Amazing Amy" with excessive improvisation